Multi-wavelength laser generation with Bismuthbased Erbium-doped fiber - Ahmad, Harith; Shahi, Sharifeh; Harun, Sulaiman Wadi (Optical Society of America, 2009)
A multi-wavelength laser comb is demonstrated using a nonlinear effect in a backward pumped Bismuth-based Erbium-doped fiber (Bi-EDF) for the first time. It uses a ring cavity resonator scheme containing a 215cm long highly nonlinear Bi-EDF, optical isolators, polarisation controller and 10dB output coupler. The laser generates more than 10 lines of optical comb with a line spacing of approximately 0.41nm at 1615.5nm region using 146mW of 1480nm pump power.